KUALITAS PELAYANAN PEMBUATAN SURAT IZIN USAHA PERDAGANGAN (SIUP) PADA BADAN PELAYANAN PERIZINAN TERPADU DAN PENANAMAN MODAL KABUPATEN DONGGALA - Rahim, Abdul (Katalogis, 2017)
This research aims to find out how the service quality on business licence making at the Integrated Licensing Bodies and Invetment of Donggala Regency. This was a qualitatif research. The informants were determined troungh purposing sampling. The data type was primary and secondary. The data were collected throungh observation, interview and documentation. The data analysis used was from Miles and Humberman interaktive analysis covering data reduktion, data display, and drawing conclusion. Theory used was from Zeithaml, Parasuraman and Berry that comprised 5 dimensions, such as: tangibles, reliabillity, responsiveness, assurace and empathy. The results reveal that service quality of business licence making at the Integrated Licensing Bodies and Investment of Donggala Regency is not maximal yet. First, on tangibles dimension still lack of facilities to support the service such as it is neater especially for four wheels vehicles. Second, on reliabillity dimension which is inaccuracy in completing the license as the standard operational procedure, third on responsiveness dimension there are still officers do not serve quickly and responsive on the complaint.